Racemose neurocysticercosis - Arushi G. Saini; Sameer Vyas; Pratibha Singhi (Elsevier, 2017)
Racemose neurocysticercosis refers to the 'aberrant proliferating cestode larvae" presenting as multiple, non-capsulated cystic membranes that bud exogenously giving a multilocular cystic appearance resembling a 'bunch of grapes'. These are typically located in non-confining areas of brain such as cisterns and lack scolex, contrast-enhancement or edema. We describe a 12-year-old boy with acute-onset headache, vomiting, drowsiness and irrelevant speech, irritability, meningismus, brisk muscle-stretch-reflexes and Babinski's sign. Magnetic resonance imaging brain revealed racemose neurocysticercosis. He received ventriculo-peritoneal shunt, oral corticosteroids and albendazole for 4 weeks. Racemose cysts in neurocysticercosis are a rare presentation in children. Treatment is difficult.Racemose neurocysticercosis refers to the 'aberrant proliferating cestode larvae" presenting as multiple, non-capsulated cystic membranes that bud exogenously giving a multilocular cystic appearance resembling a 'bunch of grapes'. These are typically located in non-confining areas of brain such as cisterns and lack scolex, contrast-enhancement or edema. We describe a 12-year-old boy with acute-onset headache, vomiting, drowsiness and irrelevant speech, irritability, meningismus, brisk muscle-stretch-reflexes and Babinski's sign. Magnetic resonance imaging brain revealed racemose neurocysticercosis. He received ventriculo-peritoneal shunt, oral corticosteroids and albendazole for 4 weeks. Racemose cysts in neurocysticercosis are a rare presentation in children. Treatment is difficult. Keywords: Racemose, Neurocysticercosis, Intraventricular, Hydrocephalus